In-situ alloying of beta titanium for implant application via laser powder bed fusion - Huang, Sheng (Nanyang Technological University, 2022)
By manufacturing biomedical β-Ti alloys with Laser Powder Bed Fusion (LPBF), the “stress shielding” problem can be alleviated through compliance matching between bones and the implant. The “stress shielding” effect occurs when the stiffness of an implant is higher than that of the bone. This will lessen the load being bore by the bone, leading to bone resorption and ultimately implant loosening. For the author’s research, manufacturing of β-Ti using LPBF was done by in-situ alloying due to its relatively lower cost, compositional flexibility as well as the potential to achieve compositionally graded parts. In this method, the required proportions of two or more constituent powders are mixed, fed through the hopper, spread over the powder bed and scanned by laser to obtain the alloyed component. However, research gaps still exist in the field of in-situ alloyed β-Ti via LPBF. For instance, the effect of biocompatible β stabilizer addition in an in-situ alloyed β-Ti is not well studied. Moreover, the relatively high melting point of biocompatible β stabilizer (e.g. Ta & Nb) led to porosity-inclusion dilemma, where the progressively higher energy density input (Ed) effectively reduces the content of unmelted inclusion, but leads to the undesirable formation of keyhole induced porosity in the alloy. The inability to build a part with sufficient quality led to limited understanding on the fracture behaviors of in-situ alloyed β-Ti, which is otherwise essential for the structural reliability of an implant. To address the research gaps, the effects of Ta addition were investigated using in-situ alloyed Ti-Ta alloys. With processing using the same laser parameters, the addition of Ta led to defects evolution from keyhole induced porosity to incomplete fusion of melt pools. Ti30Ta (wt.%) provides the optimal mechanical properties for orthopaedic applications due to its lowest elastic modulus (E) ~73 GPa while having the highest yield strength (YS) ~950 MPa. The addition of Ta refines the lath/acicular phase size which strengthens the Ti-Ta alloy up to Ti30Ta. However, the usage of Ta led to the issue of unmelted particles due to its high melting point (Tm) of 2997 °C. Hence, the study proceeded with the usage of Nb, which has lower Tm of 2468 °C and at the same time possesses similar β stabilizing characteristics as compared to Ta. Ti34Nb (wt.%) was chosen due to its similar β stabilizing tendency as Ti30Ta, in which both are near β compositions. Thereafter, a new laser scanning approach was proposed and its feasibility to resolve the porosity-inclusion dilemma was concluded. The combination of high P (~650 W or 950 W), high VL (~650 mm/s or 950 mm/s), a top-hat profile laser and a suitable stripe scanning strategy is ideal for fabricating a fully dense Ti34Nb sample with limited content of unmelted Nb inclusions. These parameters result in a slow moving, large melt pool, with a small aspect ratio and melt pool angle, in a single stripe. This ensures uniform mixing of constituents and eliminates keyhole porosities. Nevertheless, the poor ductility associated with Ti34Nb in this thesis led to initial suspicion of insufficient athermal ω suppression due to the lack of β-stabilizer. This led to further study on the fracture behaviors of Ti41Nb (wt.%) and its correlation with the structural characteristics of the material. The formation of layered composite-like mesostructure with alternated Nb deprived region and matrix region was observed, due to the inherent fast cooling rate of LPBF that limits the melting and diffusion of Nb. The crack interactions with the composite-like mesostructure strongly affects the fatigue crack growth (FCG) rate and fracture toughness in an anisotropic fashion. At high ∆K (> 7 MPa√m), the FCG underwent severe deflection in the Nb deprived region and slows down the FCG rate. Meanwhile, crack deflection occurs along the interface of Nb deprived region and matrix region during fast fracture. This improved the fracture toughness of the resultant alloy by almost two-fold despite its brittle failure response in a tensile test. All in all, the findings in this thesis contributed to the scientific knowledge that is essential to propel the application of in-situ alloyed β-Ti.